ANALISIS PENDEKATAN GESTALT DALAM PISKOLOGIS MAHASISWA - Ratu Mustarsyiddah; Qoulan Sadida; Fatiyatur Rahmah; Imalatul Khairat (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study aims to analyze the relevance and effectiveness of the Gestalt approach in addressing the psychological needs of university students. The Gestalt approach emphasizes full awareness of the present experience (here and now) as a way to resolve internal conflicts and promote psychological well-being. Through a literature review and empirical content analysis of previous studies, this research found that Gestalt-based techniques such as the empty chair, guided imagery, and role-playing are effective in helping students cope with academic stress, anxiety, procrastination, and emotional instability. Students who underwent Gestalt counseling sessions demonstrated significant improvement in self-awareness, emotional regulation, self-efficacy, and interpersonal skills. These results indicate that the Gestalt approach offers not only therapeutic benefits but also contributes to personal development and emotional resilience among university students. Furthermore, the approach aligns with the goals of humanistic education by promoting responsibility, self-reflection, and authenticity. Given its practical and philosophical strengths, the Gestalt approach is recommended as an alternative method within campus counseling services. Institutions are also encouraged to provide professional development and training for counselors to effectively implement Gestalt techniques in a contextual and culturally sensitive manner.